The Taxonomy of Traditional Surface Design Patterns in Patang - Amjad Parvez (بازیافت, 2018)
The Patang is considered the most advanced kind of kites when it comes to expert opinion. The professional kite players consider the Patang as a hallmark of expertise in kite flying. Given this importance, the Patang is prepared with exquisite surface design patterns and color schemes that refer to a thriving tradition of the Subcontinent. The design patterns range from basic to complex combinations with use of symbols and motifs and the reflect in the titles of Patangs. Moreover, the surface design patterns and their taxonomy are expressive of the Muslim and Hindu culture and show strong cultural influences. This study describes various surface design patterns used in the Patangs in terms of their intricacies and calculations.